Low Expression of Programmed Death 1 (PD-1), PD-1 Ligand 1 (PD-L1), and Low CD8+ T Lymphocyte Infiltration Identify a Subgroup of Patients With Gastric and Esophageal Adenocarcinoma With Severe Prognosis - Däster, Silvio; Eppenberger-Castori, Serenella; Mele, Valentina; Schäfer, Hannah M.; Schmid, Lukas; Weixler, Benjamin; Soysal, Savas D.; Droeser, Raoul A.; Spagnoli, Giulio C.; Kettelhack, Christoph; Oertli, Daniel; Terracciano, Luigi; et al. (Frontiers in Medicine, 2020)
Prognosis of gastric and esophageal cancer is poor and treatment improvements are needed. Programmed cell death 1 receptor (PD-1) interaction with its ligand PD-L1 in tumor micro-environment promotes immune tolerance and blocking monoclonal antibodies have entered clinical practice. However, clinical significance of PD-1 and PD-L1 expression in gastric and esophageal adenocarcinomas, particularly in non-Asian patients, is still unclear. Three tissue microarrays including 190 clinically annotated esophageal (n=31) and gastric (n=159) adenocarcinomas and 58 paired mucosa specimens, were stained with PD-1, PD-L1 and CD8-specific reagents in indirect immunohistochemistry assays. PD-L1 expression was detectable in 23.2% of cancer specimens. High PD-1 expression was detectable in 37.3% of cases and high CD8+ infiltration in 76%. PD-L1 and high PD1 expression significantly correlated with each other (rs=0.404, P<0.0001) and both significantly correlated with CD8+ infiltration (rs=0.435, P=0.0003 and rs=0.444; P=0.0004, respectively). CD8+ lymphocyte infiltration correlated with improved survival in univariate (P=0.009), but not multivariate analysis. Most interestingly, multivariate analysis and Kaplan-Meier curves indicate that combined low PD-1/PD-L1 expression and low CD8+ lymphocyte infiltration significantly correlate with poor prognosis. Our data document the clinical significance of a microenvironmental signature including PD-1/PD-L1 expression and CD8+ lymphocyte infiltration in gastric and esophageal adenocarcinomas and contribute to identify a patients’ subset requiring more aggressive peri-operative treatments.